2018
DOI: 10.1123/ijspp.2017-0421
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA as an Earlier Predictor of Exercise-Induced Performance Decrement Related to Muscle Damage

Abstract: cfDNA increases in response to RE intensity even when not performed until exhaustion. cfDNA measured immediately after RE is a promising biomarker for muscle-performance decrement up to 48 h after a RE bout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…Another interesting data observed in our study was the response of cfDNA, we and other have already demonstrated that it may be new marker of EIMD or a predictor of exercise performance 24 h after the exercise session ( Atamaniuk et al, 2010 ; Andreatta et al, 2018 ). The second mechanism is reinforced by our data since cfDNA did not increased significantly immediately after exercise in the RE40+BFR group while exercise performance was already recovered 24 h after exercise.…”
Section: Discussionsupporting
confidence: 54%
“…Another interesting data observed in our study was the response of cfDNA, we and other have already demonstrated that it may be new marker of EIMD or a predictor of exercise performance 24 h after the exercise session ( Atamaniuk et al, 2010 ; Andreatta et al, 2018 ). The second mechanism is reinforced by our data since cfDNA did not increased significantly immediately after exercise in the RE40+BFR group while exercise performance was already recovered 24 h after exercise.…”
Section: Discussionsupporting
confidence: 54%
“…The magnitude of cfDNA concentration increases also appears proportional to both exercise intensity and duration [119,120], and the time course of these changes is remarkably transient, with cfDNA concentrations often returning to baseline within 24 h, even after highly exhaustive exercise [115]. As a result, cfDNA represents a potentially novel biomarker for fatigue and recovery in exercise [113,119,120]. In subjects who undertook a 12-week resistance training intervention, cfDNA was strongly correlated with mean training load within each 3-week training sub-block [118].…”
Section: Section Summarymentioning
confidence: 95%
“…While the mechanism underpinning the increased release of cfDNA during exercise is poorly understood, it appears that cfDNA is primarily released from cells involved in immune function [119]. The magnitude of cfDNA concentration increases also appears proportional to both exercise intensity and duration [119,120], and the time course of these changes is remarkably transient, with cfDNA concentrations often returning to baseline within 24 h, even after highly exhaustive exercise [115]. As a result, cfDNA represents a potentially novel biomarker for fatigue and recovery in exercise [113,119,120].…”
Section: Section Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…This type of training has been used over the years occupying high volume load protocols (muscular endurance) 45,46 , high-intensity exercises (maximum strength) 47,48 , or muscular hypertrophy programmes 12,13 . In this sense, it has been reported that high volume muscle endurance training performed at a low-intensity of 1RM increases DOMS levels in healthy sedentary subjects (p < 0.05), regardless of whether it is performed with short intervals (1 minute) or long intervals (3 minutes) of rest between series 36 .…”
Section: Conventional Strength and Muscle Fatigue Trainingmentioning
confidence: 99%